Clinically relevant outcome measures for assessing disease activity, disease control and quality of life impairment in patients with chronic spontaneous urticaria and recurrent angioedema. Issue 3 (June 2015) - Weller, Karsten; Zuberbier, Torsten; Maurer, Marcus
Abstract : Purpose of review: The aim of this review is to highlight the most important, clinically relevant patient-reported outcome (PRO) measures for chronic spontaneous urticaria and recurrent angioedema. Recent findings: The use of PROs becomes increasingly important in modern patient-centred medicine. In the past years, several new, validated and reliable tools for the assessment of disease activity, disease control and health-related quality of life impairment of chronic spontaneous urticaria and recurrent angioedema patients have become available. These are required to optimize and standardize clinical trials. In addition, they are of increasing relevance in routine management. The major advantage of their application is that they do not only improve and standardize medical record keeping and care but also release valuable time for the actual physician–patient consultation. A prerequisite for this to work out is, however, that the PROs are well embedded into patient management. Summary: The currently available PRO measures can help to better determine the patient's disease status, to aid, document and back treatment decisions as well as to improve the assessment of treatment effects. Linguistically validated versions of the PROs are available for many but not all languages yet. Here, further research is needed to close these gaps. Abstract : Supplemental Digital Content is available in the text